A new design model for welded joints: Experimental investigations of welds on high‐strength steels. Issue 3 (29th July 2021) - Stroetmann, Richard; Kästner, Thoralf
Abstract: In the AiF‐FOSTA research project P1020 [1], a new design model for welded joints was developed. In this context, a small scale test on flat tensile specimens was designed, with the help of which various influences on the strength and ductility of the welds were investigated. Furthermore, extensive tests were carried out on overlap joints, cruciform joints with double fillet welds as well as partially and fully penetrated butt joints. This was done to calibrate the weld construction factor α w, which takes into account the influence of the type of joint on the load‐bearing capacity. In the following article, after a short summary of the current state of research, the design model, and the results from the parameter studies on flat tensile tests are described in more detail in [2–4]. Subsequently, the test program on welded joints and the calibration of the weld construction factor α w are presented. Finally, the results of the design model and the tests carried out are compared with test results from other research projects and the design model of prEN 1993‐1‐8 [5].